Polysaccharide-rich fraction of Agaricus brasiliensis enhances the candidacidal activity of murine macrophages - Martins, Priscila Raquel [UNESP]; Gameiro, Maria Carolina [UNESP]; Castoldi, Lindsey [UNESP]; Romagnoli, Graziela Gorete [UNESP]; Lopes, Fabiane Catanho [UNESP]; Pinto, Andréa Vanessa Ferreira da Silva [UNESP]; Loyola, Wagner; Kaneno, Ramon [UNESP] (Instituto Oswaldo Cruz, Ministério da Saúde, 2008)
A polysaccharide-rich fraction (ATF) of medicinal mushroom Agaricus brasiliensis was evaluated on the candidacidal activity, H2O2 and nitric oxide (NO) production, and expression of mannose receptors by murine peritoneal macrophages. Mice received three intraperitoneal (i.p.) injections of ATF and after 48 h their peritoneal resident macrophages were assayed against Candida albicans yeast forms. The treatment increased fungicidal activity and it was associated with higher levels of H2O2, whereas NO production was not affected. We also found that the treatment enhances mannose receptor expression by peritoneal macrophages, which are involved in the attachment and phagocytosis of non-opsonized microorganisms. Treatment of animals with ATF was able to enhance the clearance of C. albicans during the first 6 h after the experimental i.p. infection. Our results suggest that this extract can increase host resistance against some infectious agents through the stimulation of microbicidal activity of macrophages.
Keywords: Candida albicans; microbicidal activity; mushroom